Creating materials with a desired refraction coefficient - Ramm, A. G. (Alexander G.) (IOP ebooks. 2020 collection., 2020)
In Ramm's second edition on refraction coefficient the author shares his recipe for creating materials with a desired refraction coefficient and solves the many-body wave scattering problem for many small impedance bodies. Technical problems are described which, when solved, make this theory practically applicable. It also provides physical and mathematical arguments for the possibility to produce such particles. Inverse scattering with non-over-determined scattering data is discussed.